O PERFIL DO ALUNO E A CONSTRUÇÃO DO CONHECIMENTO: UM ESTUDO DE CASO NO CEFET MARACANÃ - Melo, Carolina Lobo dos Reis (2013)
Knowledge management is currently configured indispensable tool for business survival . With the proposal of New Public Management , in which the public sector should search rationality adminstrative private companies seeking quality services offered , it is necessary to check how these organizations operate in contemporary and to what extent can bring up relevant knowledge to the operation public entities . The survey was conducted in CEFET RJ - Unit Maracanã with students and teachers of the course Technical Directors. The main goal was to investigate whether teaching can be offered with a didactic more satisfying to get to know student profile . To this was initially do a parallel between the operation of businesses and schools . Investigated how companies currently pursue to define the profile of the clients in order to develop products that meet existing demands .In the methodology used initially teachers were asked to define the profile of their students.Then the student profile was developed through questionnaires completed by them. And last, profile was presented to teachers . It is hoped that the results obtained in this study extend the communication between teacher and students to get to know more and more about students profile generating a learning increasingly committed to the quality and training of the individual .